Letters from Skye - Brockmole, Jessica (New York Hutchinson Publishers, 2013)
A love story told in letters spans two world wars and follows the correspondence between a poet on the Scottish Isle of Skye and an American volunteer ambulance driver for the French Army, an affair that is discovered years later when the poet disappears.
Keywords: Friendship -- Letter writing -- Scotland--Island of Skye